The Effect of Tube Location on Corneal Endothelial Cells in Patients with Ahmed Glaucoma Valve - Zhang, Qi (Ophthalmology, 2020)
OBJECTIVE: To compare the effects of Ahmed glaucoma valve (AGV) with sulcus versus anterior chamber (AC) tube placement on the corneal endothelial density and morphology over time. DESIGN: Non-randomized interventional study PARTICIPANTS: This study included 106 eyes from 101 pseudophakic patients who had AGV tube placed in the AC (acAGV) and 105 eyes from 94 pseudophakic patients who had AGV tube insertion into the ciliary sulcus (sAGV). METHODS: All patients underwent preoperative specular microscopy, which was repeated postoperatively in 2019. The patients demographic information, glaucoma diagnoses, and basic ocular information were obtained on chart review. Anterior segment optical coherence tomography was conducted for sAGV patients to evaluate sulcus tube position. Gonioscopy was performed to document peripheral anterior synechiae (PAS). Linear mixed-effects models were used to compare the different ocular and endothelial measurements between the two groups and to identify risk factors for endothelial cell density (ECD) loss over time. MAIN OUTCOME MEASURES: Monthly change in corneal endothelial measurements, including ECD and coefficient of variation (CV), calculated as the difference between preoperative and postoperative measurements divided by the number of months from the time of surgery to postoperative specular microscopy. RESULTS: AcAGV and sAGV groups were comparable in all baseline characteristics except that acAGV group had longer follow up (37.6 vs. 20.1 months, respectively, P<0.001). Mean monthly loss in central ECD was significantly more in the acAGV (mean±standard deviation: 29.3±29.7 cells/mm(2)) than the sAGV group (15.3±20.7 cells/mm(2), P <0.001). Mean monthly change in CV was similar between the 2 groups (P = 0.28). Multivariate analyses revealed that younger age and tube location in the AC were associated with faster central ECD loss (P = 0.02, P<0.0001, respectively). For patients with sAGV, while PAS was associated with faster central ECD loss (P=0.002), a more forward tube position tenting the iris was not (P>0.05). CONCLUSIONS: Compared to anterior segment placement, ciliary sulcus tube implantation may be a preferred surgery approach to reduce endothelial cell loss in pseudophakic patients.